2011
DOI: 10.1017/s1751731111000838
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of non-nutritive sorbent materials as intestinal-binding agents for the control of boar taint

Abstract: In many countries, male pigs are castrated to prevent boar taint, but this practice raises concerns about animal welfare and reduces the production efficiency of pork. The objective of this study was to develop dietary manipulations to prevent boar taint. We evaluated the effectiveness of adding activated carbon (AC) or Tween-60 (Tween; polyoxyethylene sorbitan monostearate) to pig finishing diets to reduce levels of androstenone (AND) and skatole in plasma and fat of entire male pigs. Boars (159 6 2 days of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Steroids can then be reabsorbed across the intestinal wall, which enables the recycling of these steroids in a process known as the enterohepatic circulation [36]. We have proposed interrupting the enterohepatic circulation as a potential approach to decreasing boar taint from androstenone [37].…”
Section: Androstenone Metabolismmentioning
confidence: 99%
See 3 more Smart Citations
“…Steroids can then be reabsorbed across the intestinal wall, which enables the recycling of these steroids in a process known as the enterohepatic circulation [36]. We have proposed interrupting the enterohepatic circulation as a potential approach to decreasing boar taint from androstenone [37].…”
Section: Androstenone Metabolismmentioning
confidence: 99%
“…The role of the enterohepatic circulation in regulating androstenone levels is not completely understood. Proof-of-concept studies have shown that adding activated charcoal to finishing diets can decrease androstenone levels [37], but the mechanism of the enterohepatic circulation of androstenone has not been described. There is also a need to find cost effective and selective adsorbents for androstenone that can be added to finishing diets of entire males.…”
Section: Aspects That Are Not Yet Well Understoodmentioning
confidence: 99%
See 2 more Smart Citations
“…Until recently, no evidence had suggested that A tissue concentration was affected by nutrition [7]. However, Jen and Squires [8] found that the EMs fed with activated carbon for 28 days in the finishing period had lower plasma as well as tissue A levels compared to a control group. The authors hypothesized that A, like oestadriol, undergoes enterohepatic circulation [9], and activated carbon could act as an absorbent, thereby diminishing A tissue levels.…”
Section: Introductionmentioning
confidence: 99%